A Study on Teachers’ Competency In Teaching English At SMA Negeri 2 - A.E.Lao, Hendrik; Kaipatty, Gres Jekstman; Jeronimo, Agapito da Costa (Universitas Muhammadiyah Semarang, 2017)
This study is entitled; A Study on Teachers’ Competency In Teaching English At SMA Negeri 2 Kupang. It was conducted to answer the research question, “what are the teachers’ competencies in teaching English at SMA Negeri 2 Kupang?”. The methodology of this study was qualitative method. The research instruments of thi study were interview and observation. The research subject of this study were four English teachers at SMA Negeri 2 Kupang. The result of this study showed there were four competencies owned by the English teacher in teaching English at SMA Negeri 2 Kupang. The pedagogic competence was performed by the teachers in some manners such as, know the learner characteristic, understand learning theories, develop lesson plan, facilitate the students’ potential, communicate with the students, organize the process of assesment and evaluation, utilize the result of assesment and evaluation, take action to improve the quality of reflective learning. Then, the personalcompetence was performed by acting in accordinance with the norms of religious, legal, social, and national culture of Indonesia, and present self as being steady, noble, and rule models for the students, and also showed the work ethic as a teacher. Another competence owned by the teachers in teaching English was social competence. Social competence was performed by the teachers with some manners such as; act objective, be inclusive, and not discriminative, communicate effectively, adapt on duty in entire territory ofIndonesia. The last competence owned by the teachers was professional competence. The professional competence was performed by the teachers with some manners such as; understand the material, structure, concepts, and scientific mindset that support the subject matter and know the competency standards and basic competencies mastered basic subject or field of teaching development. Those are the competencies were performed by the English teachers at SMA Negeri 2 Kupang based on their ability and capability inteaching English.Key Words:Teacher, competency, teaching